1978
DOI: 10.2307/1421535
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements and a Dynamic Stimulus Situation

Abstract: Two experiments were conducted to investigate performance with and without voluntary eye movements in a dynamic stimulus situation. Experiment I used a combined tracking and prediction task. Level of training, complexity of the signal, and visual region sampled were the variables of interest. Experiment II manipulated the same variables in only the prediction task. Thus, the amount of attention allotted to the prediction task was varied between experiments. The d' measure indicated that under peripheral vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Eye movement behavior in a number of dynamic situations, such as driving (A. S. Cohen, 1981;A. S. Cohen & Studach, 1977;Dishart & Land, 1998;Land, 1992;Land & Rirneaux, 1997;Land & Horwood, 1995;Land & Lee, 1994;Liu, 1998), basketball foul shooting (Vickers, 1995(Vickers, , 1996, golf putting (Vickers, 1992), table tennis (Land & Furneaux, 1997), baseball (Bahill & LaRitz, 1984;Shank & Haywood, 1987), gymnastics (Vickers, 1988), walking in uneven terrain (Patla & Vickers, 1997), mental rotation Just & Carpenter, 1985), and interacting with computer screens (Deffner, 1995;Goldberg & Schryver, 1995;Goolkasian & Bunt, 1980;Jacob, 1991;Stampe & Reingold, 1995) have been examined. Studies in which eye-head coordination is important have revealed that although the eyes often move prior to the head, head and eye movements are generally highly coordinated in such tasks.…”
Section: Dynamic Situationsmentioning
confidence: 99%
“…Eye movement behavior in a number of dynamic situations, such as driving (A. S. Cohen, 1981;A. S. Cohen & Studach, 1977;Dishart & Land, 1998;Land, 1992;Land & Rirneaux, 1997;Land & Horwood, 1995;Land & Lee, 1994;Liu, 1998), basketball foul shooting (Vickers, 1995(Vickers, , 1996, golf putting (Vickers, 1992), table tennis (Land & Furneaux, 1997), baseball (Bahill & LaRitz, 1984;Shank & Haywood, 1987), gymnastics (Vickers, 1988), walking in uneven terrain (Patla & Vickers, 1997), mental rotation Just & Carpenter, 1985), and interacting with computer screens (Deffner, 1995;Goldberg & Schryver, 1995;Goolkasian & Bunt, 1980;Jacob, 1991;Stampe & Reingold, 1995) have been examined. Studies in which eye-head coordination is important have revealed that although the eyes often move prior to the head, head and eye movements are generally highly coordinated in such tasks.…”
Section: Dynamic Situationsmentioning
confidence: 99%